The Essential Foundation for the "Detroit of Asia" and the Approach of the Auto Parts Industry - Ruchatachat, Tanutporn (2009)
The Thai auto parts industry is considered to be, along with the automotive industry, the driving force of the nation’s economy. Dating back to the 1960s, the government has started an initiative to establish Thailand as the “Detroit of Asia”. Foreseeing that the auto parts and automotive industries are two interrelated segments with high value added, various measures and policies are planned by the government to nurture and support the two industries so that they can be internationally competitive. This paper analyzes interviews conducted with firms in the auto parts and automotive industries along with the secondary data to identify the source of competitive advantage of the auto parts industry and its contribution to the development of the automotive industry. The findings, which utilized the national diamond model, five forces framework, and network theory, has demonstrated an interesting result. The role of the government is much more important than expected. Policies and regulations enforced by the government are the main factor creating competitive advantage for the auto parts industry. Also, the unique production network of the auto parts and automotive industries has significantly shaped and contributed to the competitive advantages of the auto parts industry as well. It is hope that this paper would benefit policy makers in identifying the source of competitive advantages of the auto parts industry and help in designing new policies that will further enhance the performance of the sector, or provide an insight into the development of the auto parts industry to those interested in the industry. With the new wave of economic recession and the decrease in demand for traditional parts and components, the industry is facing challenges in the years to come.